Future energy and environment management using fuzzy linear programming including energy recovered from urban solid wastes (Case study: Iran country) - Nematian, Javad; Farzi, Yosef (Environmental progress & sustainable energy, 2017)
Energy and energy management is one of the most important subjects which concerns all the countries around the world. As fossil fuels are depleted, attention toward other energy sources increases. Renewable energy sources have become one of the popular topics in this field. Although these sources are renewable by nature, several difficulties are faced when countries attempt to implement these systems. One of these problems is the changing efficiency of renewable energy sources due to availability and quality of the sources such as sunlight intensity, wind speed, and so on. This study considers various renewable energy sources and different needs in a country. Next, a linear programming model is used to optimize the problem in deterministic form. After that, because efficiency of RES is not deterministic, in this article, we use fuzzy linear programming to handle these difficulties. To achieve this, we transform our linear model to fuzzy linear programming using theorems from literature. In this study, we used six RES plus nuclear energy to meet different electricity demand. In the end to test our FLP model, a case study in Iran, which bifurcates this country to east and west sections, each with different energy potentials, is done and the results are presented. © 2017 American Institute of Chemical Engineers Environ Prog, 36: 953–966, 2017